Effect of CsCl Additive on the Morphological and Optoelectronic Properties of Formamidinium Lead Iodide Perovskite. Issue 11 (25th September 2019) - Chavan, Rohit D.; Prochowicz, Daniel; Yadav, Pankaj; Tavakoli, Mohammad Mahdi; Nimbalkar, Ajaysing; Bhoite, Sangram P.; Hong, Chang Kook
Abstract : The quality of perovskite films plays a crucial role in improving the optoelectronic properties and performance of perovskite solar cells (PSCs). Herein, high‐quality Cs x FA1− x PbI3 perovskite films with different compositions ( x  = 0, 5, 10, and 15) are achieved by controlling the amount of cesium chloride (CsCl) in the respective FAPbI3 precursor solution. The effects of CsCl addition on the morphological and optoelectronic properties of the resulting perovskite films and on the performance of the corresponding devices are systematically studied. Introduction of CsCl into FAPbI3 shows a great potential to stabilize the α‐FAPbI3 perovskite phase by forming Cs x FA1− x PbI3 films with improved morphology and carrier lifetimes. With an optimal 10 mol% CsCl additive, the average power conversion efficiency (PCE) is increased from 16.83 ± 0.30% for the reference FAPbI3 ‐based PSCs to 18.87 ± 0.25% (with a steady‐state PCE of 18.89%). Moreover, the optimized device performance is more stable after 20 days than the controlled one under ≈40% humidity in air. Abstract : The fabrication method of high‐quality (Cs) x (FA)1− x PbI3 perovskite films by varying the amount of cesium chloride (CsCl) in the FAPbI3 precursor solutions is demonstrated. The best photovoltaic performance with a power conversion efficiency of 19.20% is achieved for the device with 10 mol% excess of CsCl.